Answer: ⇒ [tex]h=-12[/tex]
________________________________________________
Step-by-step explanation:
First you had to add by 1 from both sides of equation.
[tex]\frac{h}{6}-1+1=-3+1[/tex]
Simplify.
[tex]\frac{h}{6}=-2[/tex]
Then you multiply by 6 from both sides of equation.
[tex]\frac{6h}{6}=6(-2)[/tex]
Simplify it's should be the right answer.
[tex]h=-12[/tex]
________________________________________________________
Hope this helps!
Thank you for posting your question at here on brainly.
Have a great day!
_________________________________________________________